Autonomic function assessment in Egyptian patients with Behçet's disease: a case-control study - Anwar M Ali; Esraa A Talaat; Saber A.E.H El Nazer; Manal M Hasanein (Wolters Kluwer Medknow Publications, 2021)
Background Behçet's disease (BD) is considered a chronic multisystem disorder, where neurological manifestations are common. There is scarcity of investigations that have assessed the autonomic nervous system dysfunction in BD, with conflicting results. Objectives The current study aimed to identify presence of autonomic nervous system dysfunction using neurophysiological assessment in BD and to investigate the relationship between the indicators of autonomic function and the disease activity parameters. Patients and methods The study involved 30 patients with BD in accordance with the Universal Criteria for Behçet's Diseases and 25 controls, who were subjected to clinical evaluation and Palmar sympathetic skin response (SSR). Results Patients with BD had a significant difference in SSR (P<0.001) compared with controls. Moreover, a significant positive association was found among neuropathic pain and disease activity parameters. Conclusion The study confirms the presence of sympathetic autonomic dysfunction in BD, which related to disease activity using a simple noninvasive test such as SSR.